The Bagnold Dunes in Southern Summer: Active Sediment Transport on Mars Observed by the Curiosity Rover. Issue 17 (14th September 2018) - Baker, Mariah M.; Lapotre, Mathieu G. A.; Minitti, Michelle E.; Newman, Claire E.; Sullivan, Robert; Weitz, Catherine M.; Rubin, David M.; Vasavada, Ashwin R.; Bridges, Nathan T.; Lewis, Kevin W.
Abstract: Orbiter‐based observations have demonstrated that active aeolian environments are ubiquitous across Mars. Here we examine one such environment, the Bagnold Dune Field in Gale crater, with repeat imaging campaigns conducted from Curiosity during southern summer. Images reveal widespread migration of aeolian impact ripples (up to 2.8 cm/sol), which is in stark contrast to the inactivity of similar bedforms during southern winter. The winds responsible for steady southwestward migration of ripples are consistent with predictions of regional‐scale flows that enter the crater from the north and interact with the topography of Mount Sharp but are not fully representative of all dune‐forming winds. Inferred friction speeds of 1.5 m/s needed to explain mobilization of bedforms are likely not being achieved, and thus, a majority of sediment transport may be taking place at subthreshold conditions. This hypothesis is further supported by sand flux estimates that suggest a low saltation flux environment within the dune field. Plain Language Summary: A wealth of orbital images have revealed that wind is actively moving sand on the surface of Mars; landed instruments enable a closer look at these processes. Images acquired during southern summer by the Curiosity rover in Gale crater revealed high levels of wind activity, in contrast to previous imaging done during southern winter. A majority of ripple migration occurs toward the southwest, with ripples moving up to 2.8 cm per day. These findings are consistent with models that predict southern summer to be the windiest season at this location on Mars, with strong regional winds flowing over the northern crater rim and causing strong southwestward flow along the floor of the crater in the vicinity of the rover. Despite the fact that bedforms are active, models do not predict that the wind should be strong enough to initiate motion, which challenges our understanding of the physics of sediment transport under Martian conditions. Key Points: Curiosity's imaging campaigns in the Bagnold Dune Field reveal that impact ripples migrate up to 3 cm/sol during southern summer Impact ripples generally migrated toward the southwest within a 70 degree range about their mean migration direction Sand flux estimates are consistent with low‐flux saltation occurring below the fluid threshold of sand transport